THE EFFECT OF GHASAB ON SANTRI SUCCESS - Qur'ana, Siti Wahidatul (Journal Intellectual Sufism Research (JISR), 2020)
This research is a case study, which is an intensive and detailed intensive study of a particular organization, institution or symptom. This type of research is field research, namely research in which data collection is carried out in the field. This research is a case study, which is an intensive and detailed intensive study of a particular organization, institution or symptom.Ghasab influences one's success, Allah Almighty has explained in the Qur'an that there are 9 keys to success namely Prayer (Al-Muttaqin, Al-Baqarah: 1-5, Luqman: 5), Forming Communities That Help Each Other Toward Success, Increase Positive Activities, Follow and emulate the Messenger of Allah, Fight and Exert all efforts, Obey Allah's Orders and Laws, share with relatives and relatives (Ar-rum 38), Stay Away from Miserability, Firmness Against Infidels.